Design and Characterization of Compact Microstrip Patch Antenna Using “Split Ring” Shaped Metamaterial Structure - Bimal Garg; Pramod k Singhal (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Authors analyzed and explored asignificant concept of micro-strip patch antennaconfigured by double negative left handedmetamaterial which have dielectric permittivity &magnetic permeability both negative simultaneously.Basic aim of this paper is to explain thegeneral properties of rectangular micro-strippatch antenna with metamaterial structure likereturn loss, bandwidth, directivity and gain. Inthis paper authors have compared the return loss,bandwidth & gain of the micro-strip patchantenna at a frequency of 2GHz and height of 3.2mm from the ground plane with “SPLIT RING”Shaped double negative left-handed metamaterial.It has been observed that the return loss hasimproved by 20dB. The complex permittivity andpermeability of the proposed structure has beenextracted by Nicolson-Ross-Weir (NRW)approach.DOI:http://dx.doi.org/10.11591/ijece.v2i5.788